Penerapan Laporan Laba/Rugi Segmen Sebagai Alat Bantu Untuk Pengendalian Biaya - Neneng Dahtiah; Frita Ayuning Putri (Jurnal Accounting Information System (AIMS), 2021)
This research was conducted in the company "X" which is a company with more than one type of business activity. This research was conducted to determine how the application of the segment income statement using the contribution approach. The method used in this research is quantitative method with a case study approach, and data collection techniques using interview techniques and documentation. The segment profit / loss statement applied in this study contains the division segment profit / loss statement, the product line segment income statement, and the rental income segment report from the tenants. After the research is carried out, the segment income statement contains information that shows a number of losses on a particular product. This is because the information in the income statement prepared by the company is not detailed so that the costs incurred in the previous period were out of control.